The Effect of Perception on the Benefits of Tax toward the Discipline of Paying Taxes in Jakarta - Estiningsih, Wening; Mashita, Juni; Lestiyono, Sidik (Journal of Economic Development, Environment and People, 2019)
Perception of the benefits received by the community as compensation for paying taxes is one of the factors that influence the discipline of society in paying taxes. Thus the purpose of this study is to examine more deeply the effect of perceptions on the benefits received from paying taxes on discipline in paying taxes in Jakarta. The population in this study were individual taxpayers who work as lecturers on two campuses located in Jakarta. The number of respondents involved in the study was 56 people. The analysis method used is descriptive statistics. The results of the study show that the perception of the benefits of paying taxes will affect the willingness of the community (especially taxpayers) to pay taxes on time. So that in increasing the discipline of society, especially taxpayers, the Government needs to provide concrete examples of development that directly impact and can be felt by the community.